1998
DOI: 10.1074/jbc.273.8.4516
|View full text |Cite
|
Sign up to set email alerts
|

A Role for Superoxide in Protein Kinase C Activation and Induction of Long-term Potentiation

Abstract: The induction of several forms of long-term potentiation (LTP) of synaptic transmission in the CA1 region of the mammalian hippocampus is dependent on N-methyl-D-aspartate receptor activation and the subsequent activation of protein kinase C (PKC), but the mechanisms that underlie the regulation of PKC in this context are largely unknown. It is known that reactive oxygen species, including superoxide, are produced by N-methyl-Daspartate receptor activation in neurons, and recent studies have suggested that som… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
153
1
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(167 citation statements)
references
References 54 publications
10
153
1
3
Order By: Relevance
“…Shortly after washout of Chel, EPSPs gradually increased and reached a plateau similar to that in control neurons (Fig. 5A), consistent with the long-lasting elevation in PKC activity after LTP induction (37). In control neurons, after the full expression of LTP perisynaptic AMPARs are absent at spine surface, and LFS does not affect LTP (10).…”
Section: Synaptic Translocation Of Perisynaptic Ampars Stabilizes Botsupporting
confidence: 58%
“…Shortly after washout of Chel, EPSPs gradually increased and reached a plateau similar to that in control neurons (Fig. 5A), consistent with the long-lasting elevation in PKC activity after LTP induction (37). In control neurons, after the full expression of LTP perisynaptic AMPARs are absent at spine surface, and LFS does not affect LTP (10).…”
Section: Synaptic Translocation Of Perisynaptic Ampars Stabilizes Botsupporting
confidence: 58%
“…This is notable because persistent activation of PKC has been shown to be associated with and necessary for the expression of LTP (Klann et al, 1991(Klann et al, , 1993Wang and Feng, 1992;Sacktor et al, 1993;Hrabetova and Sacktor, 1996).…”
mentioning
confidence: 99%
“…Interestingly, previous studies suggested that reactive oxygen species can modulate PKC in vitro [52]. The activation of PKC, which phosphorylates NMDA and AMPA receptors [53][54][55], represents one of the principal biochemical pathways necessary to induce Long Term Potentiation (LTP).…”
Section: Fig 1 Representative Confocal Images Of Sod1 Immunofluorescmentioning
confidence: 99%